Non-communicable diseases: mapping research funding organisations, funding mechanisms and research practices in Italy and Germany - Victor Stephani; Silvia Sommariva; Anne Spranger; Oriana Ciani (BMC, 2017)
Abstract Background Evidence shows that territorial borders continue to have an impact on research collaboration in Europe. Knowledge of national research structural contexts is therefore crucial to the promotion of Europe-wide policies for research funding. Nevertheless, studies assessing and comparing research systems remain scarce. This paper aims to further the knowledge on national research landscapes in Europe, focusing on non-communicable disease (NCD) research in Italy and Germany. Methods To capture the architecture of country-specific research funding systems, a three-fold strategy was adopted. First, a literature review was conducted to determine a list of key public, voluntary/private non-profit and commercial research funding organisations (RFOs). Second, an electronic survey was administered qualifying RFOs. Finally, survey results were integrated with semi-structured interviews with key opinion leaders in NCD research. Three major dimensions of interest were investigated - funding mechanisms, funding patterns and expectations regarding outputs. Results The number of RFOs in Italy is four times larger than that in Germany and the Italian research system has more project funding instruments than the German system. Regarding the funding patterns towards NCD areas, in both countries, respiratory disease research resulted as the lowest funded, whereas cancer research was the target of most funding streams. The most reported expected outputs of funded research activity were scholarly publication of articles and reports. Conclusions This cross-country comparison on the Italian and German research funding structures revealed substantial differences between the two systems. The current system is prone to duplicated research efforts, popular funding for some diseases and intransparency of research results. Future research will require addressing the need for better coordination of research funding efforts, even more so if European research efforts are to play a greater role.